The Effect of Work-Life Balance, Work Discipline, And Communication on Employee Performance in The Hotel Industry (Case Study at Tandjung Sari Hotel Sanur, Bali) - Puspitawati, Ni Made Dwi; Pradnya Semita, Ni Kadek Dhea Kirana; Parwita, Gde Bayu Surya (Universitas Trisakti, 2023)
Tourism is the most famous activity in Bali. The one of the industries that supports Bali tourism is the hotel industry. Tandjung Sari Hotel Sanur, Bali is a hotel that always maintains service quality by prioritizing employee performance. Employee performance will increase if they are able to increase work-life balance, work discipline, and communication. This research aims to determine the effect work-life balance, work discipline, and communication on employee performance at Tandjung Sari Hotel Sanur, Bali. The sample in this study was all 92 employees of Tandjung Sari Hotel Sanur, Bali. The sampling technique uses a saturated sample technique. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique used is multiple linear regression analysis. The research results show that work-life balance has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, communication has a positive and significant effect on employee performance. The implications of the research show that employees who are able to maintain work-life balance and pay attention to working time and communication with fellow co-workers will achieve the employee's ability to complete work well. Keywords: work-fife balance, work discipline, communication, employee performance